Environmental Awareness, Literacy and Biodiversity Conservation Practices of Freshmen Students in Bukidnon State University, Philippines - Ejem, Lynnette; Bello, Alwielland (JPAIR Institutional Research, 2013)
The teaching of biodiversity conservation in the university level is a laudable effort of teachers. The study ascertained the environmental awareness, literacy and biodiversity conservation practices of college freshmen students in Bukidnon State University (BukSU), Malaybalay City, S.Y. 2012-2013. Data on the students' level of awareness were gathered using the survey questionnaire on environmental awareness. Generally, the BukSU college freshmen students were "very much aware" of the environmental concepts on balance of nature, pollution, stewardship, finiteness of resources, change, interdependence, diversity and stability. The freshmen students are "moving towards mastery" on environmental knowledge, environmental attitudes and values and environmental application and decision making skills. The students "often" practice biodiversity conservation measures at home, in school and in the community.
Keywords: Environmental Science; Environmental Awareness; Environmental Literacy; Biodiversity Conservation Practices; Survey Assessment; Descriptive Method; Philippines